ANALISIS FAKTOR DETERMINAN KINERJA PEGAWAI DLKH KOTA YOGYAKARTA - Rendita Kasastri; Beta Asteria (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
The research was conducted to analyze the influence of the variables of Leadership, Compensation and Work Environment on the Performance of DLHK Employees in Yogyakarta City. This type of research is a quantitative research. The sample in this study amounted to 45 employees, with data collection techniques using questionnaires. Processing the data in this research, using SPSS version 23. Research proves that the leadership variable has no effect on the performance of Yogyakarta City DLKH employees. The compensation variable has no effect on the performance of Yogyakarta City DLKH employees, and research proves that the work environment has influence on the Yogyakarta City DLKH employee performance.